Characterization of Plasmodium developmental transcriptomes in Anopheles gambiae midgut reveals novel regulators of malaria transmission. (31st October 2014) - Akinosoglou, Karolina A.; Bushell, Ellen S. C.; Ukegbu, Chiamaka Valerie; Schlegelmilch, Timm; Cho, Jee‐Sun; Redmond, Seth; Sala, Katarzyna; Christophides, George K.; Vlachou, Dina
Summary The passage through the mosquito is a major bottleneck for malaria parasite populations and a target of interventions aiming to block disease transmission. Here, we used DNA microarrays to profile the developmental transcriptomes of the rodent malaria parasite Plasmodium berghei in vivo, in the midgut of Anopheles gambiae mosquitoes, from parasite stages in the midgut blood bolus to sporulating oocysts on the basal gut wall. Data analysis identified several distinct transcriptional programmes encompassing genes putatively involved in developmental processes or in interactions with the mosquito. At least two of these programmes are associated with the ookinete development that is linked to mosquito midgut invasion and establishment of infection. Targeted disruption by homologous recombination of two of these genes resulted in mutant parasites exhibiting notable infection phenotypes. GAMER encodes a short polypeptide with granular localization in the gametocyte cytoplasm and shows a highly penetrant loss‐of‐function phenotype manifested as greatly reduced ookinete numbers, linked to impaired male gamete release. HADO encodes a putative magnesium phosphatase with distinctive cortical localization along the concave ookinete periphery. Disruption of HADO compromises ookinete development leading to significant reduction of oocyst numbers. Our data provide important insights into the molecular framework underpinning Plasmodium development in the mosquito and identifies two genes with important functions at initial stages of parasite development in the mosquito midgut.